Diabetes in ageing: pathways for developing the evidence base for clinical guidance. Issue 10 (October 2020) - Munshi, Medha N; Meneilly, Graydon S; Rodríguez-Mañas, Leocadio; Close, Kelly L; Conlin, Paul R; Cukierman-Yaffe, Tali; Forbes, Angus; Ganda, Om P; Kahn, C Ronald; Huang, Elbert; Laffel, Lori M; Lee, Christine G; et al.
Summary: Older adults with diabetes are heterogeneous in their medical, functional, and cognitive status, and require careful individualisation of their treatment regimens. However, in the absence of detailed information from clinical trials involving older people with varying characteristics, there is little evidence-based guidance, which is a notable limitation of current approaches to care. It is important to recognise that older people with diabetes might vary in their profiles according to age category, functional health, presence of frailty, and comorbidity profiles. In addition, all older adults with diabetes require an individualised approach to care, ranging from robust individuals to those residing in care homes with a short life expectancy, those requiring palliative care, or those requiring end-of-life management. In this Review, our multidisciplinary team of experts describes the current evidence in several important areas in geriatric diabetes, and outlines key research gaps and research questions in each of these areas with the aim to develop evidence-based recommendations to improve the outcomes of interest in older adults.